2020
DOI: 10.1055/s-0040-1702195
|View full text |Cite
|
Sign up to set email alerts
|

Lymphangioleiomyomatosis

Abstract: Lymphangioleiomyomatosis (LAM) is a slow albeit progressive rare neoplastic disease featured with diffuse thin-walled cysts in lungs and angiomyolipomas in kidneys. LAM affects almost exclusively women and has one of the strongest gender predispositions of any extragenital human disease. Two forms of LAM present clinically, sporadic (S-LAM) and tuberous sclerosis complex-associated (TSC-LAM). TSC is an autosomal dominant genetic multisystems neoplastic disease. A high prevalence of LAM can be detected in adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 83 publications
0
23
0
4
Order By: Relevance
“…LAM is a rare cystic lung disease mainly diagnosed in women of child-bearing age [ 1 ]. Pregnancy is one of their major concerns when patients are diagnosed with LAM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LAM is a rare cystic lung disease mainly diagnosed in women of child-bearing age [ 1 ]. Pregnancy is one of their major concerns when patients are diagnosed with LAM.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation should include (1) the degree of LAM on high-resolution CT, (2) baseline pulmonary function and pulmonary function decline rate, (3) previous history of pneumothorax or chylothorax, (4) existence and sizes of kidney AML or retroperitoneal lymphangioleiomyomas, (5) TSC, (6) sirolimus treatment, and (7) previous history of pregnancy. A multidisciplinary team including obstetricians, pulmonary physicians, thoracic surgeons, urologists, interventional radiologists, and geneticists is recommended to ensure optimal management during pregnancy [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a recent study found that estrogen increases membrane translocation of glucose transporters and enhances glucose uptake in a PI3K/Akt-dependent way in mTORC1 hyperactive cells ( 64 ). Estrogen promotes glucose metabolism including upregulating the expression of glucose-6-phosphate dehydrogenase (G6PD) and increasing nicotinamide adenine dinucleotide phosphate (NADPH) and ROS production, and thereby promotes cell survival under oxidative stress ( 65 ). A randomized controlled trial of letrozole (a non-steroidal, competitive aromatase inhibitor lowering serum estrone and estradiol) for postmenopausal women with LAM showed that the rate of change for serum VEGF-D between placebo group and letrozole group was −0.024±0.009 pg/ml/month ( P = 0.015), but the rate of change in FEV 1 for all subjects was −3 ± 3 ml/month ( P = 0.4) ( 66 ).…”
Section: Hormones and Compensatory Erk Pathwaymentioning
confidence: 99%
“…[5] The clinical manifestations of LAM patients include progressive dyspnea after activities, recurrent spontaneous pneumothorax, refractory chylothorax and finally lead to respiratory failure. [6] Methods used to assess the severity and progression of pulmonary involvement in LAM include arterial blood gas (ABG), St. George's Respiratory Questionnaire (SGRQ), six-minute walk test (6MWT), pulmonary function test (PFT), and highresolution computed tomography (HRCT). [7] Serum levels of vascular endothelial growth factor (VEGF-D) is a diagnostic biomarker of LAM and associated with severity of LAM.…”
Section: Introductionmentioning
confidence: 99%